3D Scanning of Workpieces with Cooperative Industrial Robot Arms - Wagner, Maximilian; Heß, Peter; Reitelshöfer, Sebastian; Franke, Jörg (Proceedings of ISR 2016: 47st International Symposium on Robotics, 2016)
This paper describes the realization of a cooperative scanning approach by two industrial robot arms. The basic idea is the distribution of the movements on two robots by one robot handling the sensor and the other one handling the workpiece. Through this approach reachability is improved. In addition, the reference between the workpiece and the grasping robot is included in the scan model. Thus, the resulting model can be used well for subsequent workpiece related machining processes.

Accuracy Analysis and Improvement for Cooperative Industrial Robots - Buschhaus, Arnd; Wagner, Maximilian; Franke, Jörg; Reitelshöfer, Sebastian; Heß, Peter (Proceedings of the 14th International Conference on Informatics in Control, Automation and Robotics, 2017)

Automated programming of cooperating industrial robots - Wagner, Maximilian; Reitelshöfer, Sebastian; Heß, Peter (ISR/Robotik 2014; 41st International Symposium on Robotics, 2014)
Due to the technological development, products are becoming increasingly complex. In order to implement their sophisticated manufacturing processes, more and more often cooperative industrial robots are used. The challenge in cooperative applications is the complicated programming. Using an automated programming that is done by a generator is a corrective for this. The aim of the project described here is to divide application processes on two industrial robots by one robot holding the tool and the other one the workpiece. The adhesive or sealant application serves as an example for this. The process movements are effectively divided between the two robots in consideration of boundary conditions. To enable programming of such complex tasks for non-experts, an automated program generation with an intuitive programming interface is used.

Data fusion between a 2D laser profile sensor and a camera - Wagner, Maximilian; Heß, Peter; Reitelshöfer, Sebastian; Franke, Jörg (2015 12th International Conference on Informatics in Control, Automation and Robotics (ICINCO), 2015)
This paper describes a color extension of a 2D laser profile sensor by extracting the corresponding color from a camera image. For these purpose, we developed a routine for an extrinsic calibration between the profile sensor and the camera. Based on the resulting translation and rotation vectors a belonging pixel can be calculated for each profile point. Consequently, the color for each profile point can be extracted from the image. This approach is used to extend the geometric data of a robotic based 3D scanning system by color data.
Keywords: calibration; cameras; geometry; image colour analysis; image fusion; image resolution; image sensors; robot vision; 2D laser profile sensor; camera image; color data; color extension; data fusion; extrinsic calibration; image profile point extraction; robotic based 3D scanning system; rotation vectors; translation vectors; Calibration; Cameras; Image color analysis; Robot kinematics; Robot sensing systems; Three-dimensional displays; 3D Reconstruction; Calibration; Color Extension; Sensor Data Fusion; Workpiece Scanning

Inline calibration method for robot supported process tasks with high accuracy requirements - Buschhaus, Arnd; Wagner, Maximilian; Franke, Jörg (2017 IEEE International Conference on Advanced Intelligent Mechatronics (AIM), 2017)

Self-calibration method for a robotic based 3D scanning system - Wagner, Maximilian; Heß, Peter; Reitelshöfer, Sebastian; Franke, Jörg (2015 IEEE 20th Conference on Emerging Technologies Factory Automation (ETFA), 2015)
This paper describes a method for extrinsic sensor calibration for a 2D laser profile sensor on a robot arm used as a robot based 3D scanning system. In order to establish a relationship between the sensor measurements and the robot positions, the transformation between the robot flange and the sensor reference frame are determined. The developed calibration method is implemented as an automated self-calibration. It is based on the use of a pin as a fixed reference. The robot is aligned to the tip of the pin automatically with certain orientations. The sensor transformation is calculated based on six recorded robot positions. Finally, the accuracy of the calibration is determined with an additional robot position.
Keywords: calibration; manipulators; optical scanners; self-adjusting systems; 2D laser profile sensor; automated self-calibration; extrinsic sensor calibration; robot arm; robot flange; robotic based 3D scanning system; self-calibration method; sensor measurements; sensor reference frame; sensor transformation; Accuracy; Calibration; Robot kinematics; Robot sensing systems; Solid modeling; Three-dimensional displays